Strength training for middle- and long-distance performance: A meta-analysis - Berryman, N.; Mujika, I.; Arvisais, D.; Roubeix, M.; Binet, C.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess the net effects of strength training on middle- and long-distance performance through a meta-analysis of the available literature. Methods: Three databases were searched, from which 28 of 554 potential studies met all inclusion criteria. Standardized mean differences (SMDs) were calculated and weighted by the inverse of variance to calculate an overall effect and its 95% confidence interval (CI). Subgroup analyses were conducted to determine whether the strength-training intensity, duration, and frequency and population performance level, age, sex, and sport were outcomes that might influence the magnitude of the effect. Results: The implementation of a strength-training mesocycle in running, cycling, cross-country skiing, and swimming was associated with moderate improvements in middle- and long-distance performance (net SMD [95%CI] = 0.52[0.33-0.70]). These results were associated with improvements in the energy cost of locomotion (0.65 [0.32-0.98]), maximal force (0.99 [0.80-1.18]), and maximal power (0.50 [0.34-0.67]). Maximal-force training led to greater improvements than other intensities. Subgroup analyses also revealed that beneficial effects on performance were consistent irrespective of the athletes` level. Conclusion: Taken together, these results provide a framework that supports the implementation of strength training in addition to traditional sport-specific training to improve middle- and long-distance performance, mainly through improvements in the energy cost of locomotion, maximal power, and maximal strength. Abstract from author